Opinion 2/13 - Burkelc Juras, Lina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2019)
In a controversial Opinion 2/13, the Court of Justice of the European Union (CJEU) took a clear and unequivocal position - the Draft Agreement on the EU's accession to the European Convention on Human Rights (ECHR) is incompatible with Article 6(2) of the Treaty on EU or with Protocol No. 8 to the ECHR. Consequently, the agreement envisaged cannot enter into force unless it is amended accordingly or amended in the Treaties. Opinion 2/13 presents a significant challenge on the path of the EU accession to the ECHR, but in no case does it eliminate or undermine any association obligations. Therefore, the key to Opinion 2/13 will be to find a path that will lead to joining, which is not likely to be easy, but it is feasible. If the process of association is to be implemented in a professional manner, with expert arguments, and everyday politics do not prevail, it is considered that some changes to the Draft Agreement will be possible in the direction indicated by the CJEU. If and to the extent that it does not occur, this should not be attributed (only) to the CJEU. Let us not forget that in the Treaties, the Member States have not only set the EU's obligation to join the ECHR, but have joined the association with certain conditions that the CJEU simply had to take into account. It should also be noted that the Member States, if they reach a consensus, as the "master of the Treaties", always have the option to amend the Treaty accordingly (currently, it is more or less clear that the revision of the Treaty of Lisbon is necessary, even more realistically than at the time Opinion 2/13 was delivered). On the other hand, the CJEU does not, of course, have the possibility to review the Treaty of Lisbon, but it must accept the content of the Treaties.
Keywords: autonomy of EU law; avtonomija prava EU; Court of Justice of the European Union; European Convention on Human Rights; Evropska konvencija o človekovih pravicah; Mnenje 2/13; Opinion 2/13; Sodišče EU